Simulation and Analysis of Flexible Piezoelectric Beam under Karmen Vortex Street Effect. (August 2019) - Li, Haining; Wang, Haifeng; Sun, Kaili; Guo, Xiuyu
Abstract: Recent years, researchers have gradually increased their research efforts on energy harvesters for low power applications. Among them, many piezoelectric energy harvesters have been widely used because of their simple structures, low energy consumption and easy miniaturization. In order to study the energy harvesting with a flexible piezoelectric beam deformed by vortex-induced vibration, this paper takes polyvinylidene fluoride as the piezoelectric beam, and relies on ANSYS simulation software, establishes a fluid-solid-piezoelectric three-field coupling model, and calculates the energy harvesting capacity of piezoelectric beam. The results show that the positive output voltage is 59.763V and the negative output voltage is -67.633V.